Pengaruh Minat Belajar dengan Model Problem Based Learning Berbantuan Media Powtoon terhadap Hasil Belajar Siswa - Lamtiur Girsang; Ani Sutiani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study tested the effectiveness of an innovative combination of Problem-Based Learning (PBL) and Powtoon in improving the interest and learning outcomes of eleventh-grade high school students in thermochemistry. A quasi-experimental method with a nonequivalent control group showed a significant increase in learning interest (N-Gain 55.4%) and learning outcomes (N-Gain 77.7%) in the experimental class, with a statistically significant difference (p<0.05) compared to the control class. The PBL-Powtoon combination proved effective in overcoming the difficulties of abstract and teacher-centered thermochemistry learning, while offering a more interactive and student-centered learning approach. These findings provide an important contribution to the development of technology-based chemistry learning media, particularly for improving understanding of complex concepts.